Features and properties of viral and non-viral gene delivery systems towards effective gene therapy - Shettima, Abubakar; Ibrahim, Muhammad M.; Ibn Abbas, Musa (International Journal of Medicine, 2017)
Gene therapy has revolutionized the treatment of hereditary and genetic link disorders by consciously swapping, fixing, adding or deleting the genetic sequences responsible for the condition. The culprit cells are altered by inserting purposeful genes and incorporated into their genome for proper expression. Germ line therapy ensures the genotypic changes to be transferred to the next generation (offspring) while the somatic type adequately rest on corrective pedestals and as such not advantageous to the offspring. The earlier was constrained by technical difficulties as well as ethical consideration. The accomplishment of the therapeutic benefits of gene therapy requires a special ferry system â€œvectorsâ€. Vectors are designed to transfer the desired gene into its target cell without exposing it to some degrading enzymes, and must allow transcription to successfully take place. A model vector must not be immunogenic, it must not trigger high immune response detrimental to the patient and a specific tropism must be a pre-requisite. The choice of a vector should be based on safety, cost and availability as well as the accessibility of possible options. Mainly for viral carriers, host immune response trigger are the main concern. Viral vectors most frequently used in gene therapy include adenoviruses, retroviruses, poxviruses, adeno-associated viruses and herpes simplex viruses.